Preface. Conference Committees (Вопросы атомной науки и техники, 2007)
This issue of the Journal PROBLEMS OF ATOMIC SCIENCE AND TECHNOLOGY consists of two parts and contains communications presented at the 2-d International Conference on Quantum Electrodynamics and Statistical Physics (QEDSP2006). The Conference was held in Kharkov, Ukraine, from September 19 to September 23, 2006. It took place at the National Science Center “Kharkov Institute of Physics and Technology” (NSC KIPT).